Investigation of methodologies for fiberglass resin removal from bone - Thew, Mellisa (My University, 2015)
A human skeleton that had formerly been used as a theatrical stage prop was improperly conserved using fiberglass resin, making it unsuitable for teaching collections. This project evaluates the use of solvents and heat for removing fiberglass from bone, in an attempt to return this skeleton to a more useful, and ethically responsible, condition.
Presented April 30–May 1, 2015 at the Undergraduate Research in Science Conference of Alberta held at MacEwan University in Edmonton, Alberta.
Keywords: archaeological conservation; human bone